Inflammation in the Pathogenesis of Lyme Neuroborreliosis - Ramesh, Geeta (Am J Pathol, 2015)
Lyme neuroborreliosis, caused by the spirochete Borrelia burgdorferi, affects both peripheral and central nervous systems. We assessed a causal role for inflammation in Lyme neuroborreliosis pathogenesis by evaluating the induced inflammatory changes in the central nervous system, spinal nerves, and dorsal root ganglia (DRG) of rhesus macaques that were inoculated intrathecally with live B. burgdorferi and either treated with dexamethasone or meloxicam (anti-inflammatory drugs) or left untreated. ELISA of cerebrospinal fluid showed significantly elevated levels of IL-6, IL-8, chemokine ligand 2, and CXCL13 and pleocytosis in all infected animals, except dexamethasone-treated animals. Cerebrospinal fluid and central nervous system tissues of infected animals were culture positive for B. burgdorferi regardless of treatment. B. burgdorferi antigen was detected in the DRG and dorsal roots by immunofluorescence staining and confocal microscopy. Histopathology revealed leptomeningitis, vasculitis, and focal inflammation in the central nervous system; necrotizing focal myelitis in the cervical spinal cord; radiculitis; neuritis and demyelination in the spinal roots; and inflammation with neurodegeneration in the DRG that was concomitant with significant neuronal and satellite glial cell apoptosis. These changes were absent in the dexamethasone-treated animals. Electromyography revealed persistent abnormalities in F-wave chronodispersion in nerve roots of a few infected animals; which were absent in dexamethasone-treated animals. These results suggest that inflammation has a causal role in the pathogenesis of acute Lyme neuroborreliosis.